EMOTIONAL INTELLIGENCE AND ACADEMIC SUCCESS: RETHINKING SOCIO-EMOTIONAL LEARNING IN DIGITAL CLASSROOMS - Sofia F Rahmani; Rinda Riztya; Jeprianto Jeprianto (International Journal of Teaching and Learning, 2025)
The transformation of education toward a digital ecosystem has brought significant changes to the dynamics of learning, social interactions, and emotional well-being of students. In this context, emotional intelligence is a crucial factor in determining academic success, especially amidst the increasing reliance on distance learning technology. This study, titled "Emotional Intelligence and Academic Success: Rethinking Socio-Emotional Learning in Digital Classrooms," uses a literature review method to analyze the relationship between emotional intelligence, socio-emotional learning (SEL), and academic success in a digital environment. Through the exploration and analysis of various current academic sources, this study found that emotional intelligence plays a crucial role in developing students' self-regulation, empathy, and collaboration skills, which directly impact learning outcomes. Social-emotional learning integrated into digital classrooms has been shown to create a balance between cognitive and affective aspects, thus supporting both academic achievement and student psychological well-being. The study's findings also emphasize the need for a humanistic and reflective pedagogical approach in digital learning design, so that students not only develop intellectually but also develop emotional intelligence adaptive to the challenges of the digital era.